Impact of the H1N1 Influenza A virus epidemic on cancer treatment in Hyogo, Japan - Nakada, Haruka; Tsubokura, Masaharu; Matsumura, Tomoko; Kodama, Yuko; Kami, Masahiro; Nishimoto, Hiroshi (International Journal of Infection Control, 2011)
The rapid spread of H1N1 influenza infection had impacts on healthcare systems. However, the impact on cancer treatment remains unknown. We sent questionnaires to 14 hospitals designated by the government as cancer treatment facilities in Hyogo and collected the following data: characteristics of hospitals, the number of cancer surgeries performed, establishment of specialized departments to treat H1N1 influenza patients, and the number of cancellations and postponements of surgeries. The study period was divided into three stages; the period from March 28 to May 15, 2009 as the pre-epidemic stage, that from May 16 to June 5 as the epidemic stage, and that from June 6 to July 3 as the post-epidemic stage. We compared the data collected during the three periods to investigate the influence of H1N1 influenza epidemic on cancer treatment. We received responses from 11 (78.6%) hospitals. Of these, 10 were general hospitals with more than 300 beds and 1 was a cancer centre. Of the 11 hospitals, 7 (68.4%) had established specialized departments to treat H1N1 influenza patients. Six hospitals had only outpatient departments and 1 had an outpatient department and an inpatient department. In 5 hospitals, surgeons were engaged in the treatment of H1N1 influenza patients.The number of cancellations or postponements in the pre-epidemic, epidemic and post-epidemic stage was 16, 10 and 7, respectively. No significant difference was found among the three periods in cancellation rate. H1N1 influenza epidemic did not directly influence the cancellation or postponement of performed for cancer patients. The impact of H1N1 influenza epidemic on the number of cancer surgeries performed was minimal.